Uticaj na nivo Hba1c starosti i pola kod odraslih bez dijabetes melitusa - Şener, Gülsen; Kahvecioğlu , Esra Deniz; Gümüş, Alper; Evran, Betül (Journal of Medical Biochemistry, 2023)
Background: Hemoglobin A1c (HbA1c) levels play an important role in the diagnosis, screening, and monitoring of treatment in diabetes. The aim of our study is to determine whether there is a relationship between HbA1c levels and age and gender in Turkish adults who have not been diagnosed with diabetes.Materials and Methods: This retrospective study included 6776 Turkish adults with no known diabetes. Cross-sectional analyzes of A1C levels were performed between different age and gender categories. In statistical analysis, t-test, linear regression analysis, one-way ANOVA analysis, and LSD post hoc were used.Results: HbA1c levels in the individuals examined by dividing into different age groups increased with age in all groups. In our study, HbA1c levels were significantly higher in males than females (p < 0.001) in all groups, especially between the ages of 30-49, and were positively associated with age for males and females. There was a positive correlation between HbA1c and age in both men and women aged 30-49 years (P < 0.05). In the HbA1c ≥ 6.5% group newly diagnosed with diabetes, HbA1c levels gradually decreased with age in both genders, and no significant effect of age on Hb1Ac level was detected (p > 0.05). Conclusions: Our results showed that it is important to evaluate the effects of age and gender when using HbA1c levels in the diagnosis, screening, and treatment of diabetes, especially in the young and middle-aged population. Applying this situation to daily practice may reduce the misdiagnosis of diabetes in elderly patients, overtreatment of diabetes, and its associated risks.